DETERMINANT AGE AT FIRST MARRIAGE AMONG WOMEN IN EAST JAVA - Ali Imron; Siti Maizul Habibah; Udin Kurniawan Aziz (Universitas Airlangga, 2020)
Indonesia is one of the countries with the highest percentage of child marriages in the world (rank 37) and the second highest in ASEAN after Cambodia. Government has issued regulations in order to reduce child marriage rates, however the results are still not significant. Economic, social, and cultural factors are significant factors in child marriage phenomenon. This study aims to analyze the relationship between spouses' age, knowledge of Adolescent Reproductive Health, age when first sexual intercourse happened, education, spouses' education, media exposure, wealth quintile index and the age of first marriage for women in East Java. This study is non-functional research using The Indonesian Demographic and Health Survey 2017 (IDHS) data with a sample size as many as 4,491 women whom got married at 15–24 years old. Data were analyzed using univariate and multivariate techniques. The results of this study prove that the spouses' age, knowledge of Adolescent Reproductive Health, age when first sexual intercourse happened, education, spouses' education, media exposure, wealth quintile index variables are significantly related to the determinants of women's first marriage age in East Java. This study provides recommendations, including revitalizing 8 family functions, strengthening creativity and innovation in the Marriage Age Maturing program, and fostering life skills through training and empowerment programs.